Creation of vortices by torque in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Meier, Torsten; Malomed, Boris A. (Scientific Reports)
Recently, a new class of nonlinear systems was introduced, in which the self-trapping of fundamental and vortical localized modes in space of dimension D is supported by cubic self-repulsion with a strength growing as a function of the distance from the center, r, at any rate faster that rD. These systems support robust 2D and 3D modes which either do not exist or are unstable in other nonlinear systems. Here we demonstrate a possibility to create solitary vortices in this setting by applying a phase-imprinting torque to the ground state. Initially, a strong torque completely destroys the ground state. However, contrary to usual systems, where the destruction is irreversible, the present ones demonstrate a rapid restabilization and the creation of one or several shifted vortices orbiting the center. For the sake of comparison, we show analytically that, in the linear system with a 3D trapping potential, the action of a torque on the ground state is inefficient and creates only even-vorticity states with a small probability.

Creation of vortices by torque in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Meier, Torsten; Malomed, Boris A. (Scientific Reports)
Recently, a new class of nonlinear systems was introduced, in which the self-trapping of fundamental and vortical localized modes in space of dimension D is supported by cubic self-repulsion with a strength growing as a function of the distance from the center, r, at any rate faster that rD. These systems support robust 2D and 3D modes which either do not exist or are unstable in other nonlinear systems. Here we demonstrate a possibility to create solitary vortices in this setting by applying a phase-imprinting torque to the ground state. Initially, a strong torque completely destroys the ground state. However, contrary to usual systems, where the destruction is irreversible, the present ones demonstrate a rapid restabilization and the creation of one or several shifted vortices orbiting the center. For the sake of comparison, we show analytically that, in the linear system with a 3D trapping potential, the action of a torque on the ground state is inefficient and creates only even-vorticity states with a small probability.

Non-coaxial vortices in two-component Bose-Einstein condensates: Persistent precession and nutation - Meier, Torsten; Driben, R.; Konotop, V.V. (arXiv preprint arXiv:1505.04113)
It is demonstrated that a two-component Bose-Einstein condensate (BEC) with all-repulsive inter-atomic interactions loaded into a radially symmetric harmonic trap supports robust non-coaxial vortices with approximately orthogonal vortex lines in each of the components. These cross vortices are excited from the linear modes by a sudden switch-on of the nonlinearity (via Feshbach resonance) and are characterized by persistent dynamical regimes of precession with nutation, resembling the motion of a rigid body. The obtained dynamics can be understood qualitatively on the basis of a simple mechanical model.

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)
The Kane–Mele model was previously used to describe effective spin–orbit couplings (SOCs) in graphene. Here we extend this model and also incorporate curvature effects to analyze the combined influence of SOC and curvature on the band structure of carbon nanotubes (CNTs). The extended model then reproduces the chirality-dependent asymmetric electron-hole splitting for semiconducting CNTs and in the band structure for metallic CNTs shows an opening of the band gap and a change of the Fermi wave vector with spin. For chiral semiconducting CNTs with large chiral angle we show that the spin-splitting configuration of bands near the Fermi energy depends on the value of $\text{mod}(2n+m,3)$ .

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A.; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (SPIE Proceedings Vol. 9361: Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Interaction of high-order solitons with external dispersive waves - Meier, Torsten; Oreshnikov, I.; Driben, R.; Yulin, A.V. (Optics Letters)
The effect of mutual interaction between second-order soliton and dispersive waves (DWs) is investigated. It is predicted analytically and confirmed numerically that DWs (both transmitted and reflected components) become polychromatic after interaction with the soliton. Collision with DWs of considerable intensity can lead to acceleration/deceleration and central frequency shift of the soliton, while still preserving the soliton’s oscillating structure. Two second-order solitons with resonant DWs trapped between them can form an effective solitonic cavity with “flat” or “concave mirrors,” depending on the intensity of the input.

Sub-cycle control of terahertz high-harmonic generation by dynamical Bloch oscillations - Meier, Torsten; Schubert, O.; Hohenleutner, M.; Langer, F.; Urbanek, B.; Lange, C.; Huttner, U.; Golde, D.; Kira, M.; Koch, S. W.; Huber, R. (Nature Photonics)
Ultrafast charge transport in strongly biased semiconductors is at the heart of high-speed electronics, electro-optics and fundamental solid-state physics1,2,3,4,5,6,7,8,9,10,11,12,13. Intense light pulses in the terahertz spectral range have opened fascinating vistas14,15,16,17,18,19,20,21. Because terahertz photon energies are far below typical electronic interband resonances, a stable electromagnetic waveform may serve as a precisely adjustable bias5,11,17,19. Novel quantum phenomena have been anticipated for terahertz amplitudes, reaching atomic field strengths8,9,10. We exploit controlled (multi-)terahertz waveforms with peak fields of 72 MV cm−1 to drive coherent interband polarization combined with dynamical Bloch oscillations in semiconducting gallium selenide. These dynamics entail the emission of phase-stable high-harmonic transients, covering the entire terahertz-to-visible spectral domain between 0.1 and 675 THz. Quantum interference of different ionization paths of accelerated charge carriers is controlled via the waveform of the driving field and explained by a quantum theory of inter- and intraband dynamics. Our results pave the way towards all-coherent terahertz-rate electronics.

Adiabatic tracking of quantum many-body dynamics - Saberi, H.; Opatrný, T.; Mølmer, K.; del Campo,, A. (Physical Review A)
The nonadiabatic dynamics of a many-body system driven through a quantum critical point can be controlled using counterdiabatic driving, where the formation of excitations is suppressed by assisting the dynamics with auxiliary multiple-body nonlocal interactions. We propose an alternative scheme which circumvents practical challenges to realize shortcuts to adiabaticity in mesoscopic systems by tailoring the functional form of the auxiliary counterdiabatic interactions. A driving scheme resorting in short-range few-body interactions is shown to generate an effectively adiabatic dynamics.

Coherent bloch oscillations driven by ultrastrong THz excitation - Meier, Torsten (Frontiers in Optics 2014, OSA Technical Digest)
The carrier wave of high-intensity phase-locked multi-THz pulses controls dynamical Bloch oscillations and interband polarization in bulk semiconductors, leading to the emission of all-coherent high-order harmonics covering 12.7 optical octaves from THz to VIS regimes.

CEP control of dynamical Bloch oscillations in a bulk semiconductor via ultra-intense multi-THz fields - Meier, Torsten; Langer, F.; Schubert, O.; Hohenleutner, M.; Urbanek, B.; Lange, C.; Huttner, U.; Golde, D.; Kira, M.; Koch, S.W.; Huber, R. (CLEO: QELS_Fundamental Science)
Dynamical Bloch oscillations and coherent interband polarization in bulk GaSe are controlled by CEP-stable, ultra-intense multi-THz waveforms and result in the emission of phase-stable high-order harmonics covering 12.7 optical octaves from THz to VIS regimes.

Three-dimensional hybrid vortex solitons - Driben, Rodislav; Kartashov, Yaroslav V.; Malomed, Boris A.; Meier, Torsten; Torner, Lluis (New Journal of Physics)
We show, by means of numerical and analytical methods, that media with a repulsive nonlinearity which grows from the center to the periphery support a remarkable variety of previously unknown complex stationary and dynamical three-dimensional (3D) solitary-wave states. Peanut-shaped modulation profiles give rise to vertically symmetric and antisymmetric vortex states, and novel stationary hybrid states, built of top and bottom vortices with opposite topological charges, as well as robust dynamical hybrids, which feature stable precession of a vortex on top of a zero-vorticity soliton. The analysis reveals stability regions for symmetric, antisymmetric, and hybrid states. In addition, bead-shaped modulation profiles give rise to the first example of exact analytical solutions for stable 3D vortex solitons. The predicted states may be realized in media with a controllable cubic nonlinearity, such as Bose–Einstein condensates.

Soliton gyroscopes in media with spatially growing repulsive nonlinearity - Meier, Torsten; Driben, R.; Kartashov, Y. V.; Malomed, B. A.; Torner, L. (Physical review letters)
We find that the recently introduced model of self-trapping supported by a spatially growing strength of a repulsive nonlinearity gives rise to robust vortex-soliton tori, i.e., three-dimensional vortex solitons, with topological charges S≥1. The family with S=1 is completely stable, while the one with S=2 has alternating regions of stability and instability. The families are nearly exactly reproduced in an analytical form by the Thomas-Fermi approximation. Unstable states with S=2 and 3 split into persistently rotating pairs or triangles of unitary vortices. Application of a moderate torque to the vortex torus initiates a persistent precession mode, with the torus’ axle moving along a conical surface. A strong torque heavily deforms the vortex solitons, but, nonetheless, they restore themselves with the axle oriented according to the vectorial addition of angular momenta.

Theory of filtered type-II parametric down-conversion in the continuous-variable domain: Quantifying the impacts of filtering - Christ, Andreas; Lupo, Cosmo; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (Physical Review A)
Parametric down-conversion (PDC) forms one of the basic building blocks for quantum optical experiments. However, the intrinsic multimode spectral-temporal structure of pulsed PDC often poses a severe hindrance for the direct implementation of the heralding of pure single-photon states or, for example, continuous-variable entanglement distillation experiments. To get rid of multimode effects narrowband frequency filtering is frequently applied to achieve a single-mode behavior. A rigorous theoretical description to accurately describe the effects of filtering on PDC, however, is still missing. To date, the theoretical models of filtered PDC are rooted in the discrete-variable domain and only account for filtering in the low-gain regime, where only a few photon pairs are emitted at any single point in time. In this paper we extend these theoretical descriptions and put forward a simple model, which is able to accurately describe the effects of filtering on PDC in the continuous-variable domain. This developed straightforward theoretical framework enables us to accurately quantify the tradeoff between suppression of higher-order modes, reduced purity, and lowered Einstein–Podolsky–Rosen entanglement, when narrowband filters are applied to multimode type-II PDC.

Phase-locked multi-THz high-harmonic generation by dynamical bloch oscillations in bulk semiconductors - Meier, Torsten; Hohenleutner, M.; Schubert, O.; Langer, F.; Urbanek, B.; Lange, C.; Huttner, U.; Golde, D.; Kira, M.; Koch, S.W.; Huber, R. (19th International Conference on Ultrafast Phenomena)
Ultra-intense and CEP-stable waveforms in the multi-THz range control dynamical Bloch oscillations and interband polarization in bulk GaSe, leading to the emission of all-coherent high-order harmonics covering 12.7 optical octaves from THz to VIS regimes.

Nonlinear dynamics of Airy-vortex 3D wave packets: emission of vortex light waves - Driben, Rodislav; Meier, Torsten (Optics Letters)
The dynamics of 3D Airy-vortex wave packets is studied under the action of strong self-focusing Kerr nonlinearity. Emissions of nonlinear 3D waves out of the main wave packets with the topological charges were demonstrated. Because of the conservation of the total angular momentum, charges of the emitted waves are equal to those carried by the parental light structure. The rapid collapse imposes a severe limitation on the propagation of multidimensional waves in Kerr media. However, the structure of the Airy beam carrier allows the coupling of light from the leading, most intense peak into neighboring peaks and consequently strongly postpones the collapse. The dependence of the critical input amplitude for the appearance of a fast collapse on the beam width is studied for wave packets with zero and nonzero topological charges. Wave packets carrying angular momentum are found to be much more resistant to the rapid collapse.

Coupled Airy breathers - Driben, R.; Konotop, V. V.; Meier, Torsten (Optics Letters)
The dynamics of two component-coupled vectorial Airy beams is investigated. In the linear propagation regime, a complete analytic solution describes the breather-like propagation of two components that feature nondiffracting self-accelerating Airy behavior. The superposition of two beams with different input properties opens the possibility of designing more complex nondiffracting propagation scenarios. In the strongly nonlinear regime, the dynamics remain qualitatively robust as is revealed by direct numerical simulations. Because of the Kerr effect, the two beams emit solitonic breathers whose coupling period is compatible with the remaining Airy-like beams. The results of this study are relevant for the description of photonic and plasmonic beams that propagate in coupled planar waveguides, as well as for birefrigent or multiwavelength beams.

Engineering plasmonic and dielectric directional nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens (Ultrafast Phenomena and Nanophotonics XVIII)
Optical and infrared antennas provide a promising way to couple photons in and out of nanoscale structures. As counterpart to conventional radio antennas, they are able to increase optical felds in sub-wavelength volumes, to enhance excitation and emission of quantum emitters or to direct light, radiated by quantum emitters. The directed emission of these antennas has been mainly pursued by surface plasmon based devices, e.g. Yagi-Uda like antennas, which are rather complicated due to the coupling of several metallic particles. Also, like all metallic structures in optical or infrared regime, these devices are very sensitive to fabrication tolerances and are affected by strong losses. It has been shown recently, that such directed emission can be accomplished by dielectric materials as well. In this paper we present an optimization of nanoscopic antennas in the near infrared regime starting from a metallic Yagi-Uda structure. The optimization is done via a particle-swarm algorithm, using full time domain finite integration simulations to obtain the characteristics of the investigated structure, also taking into account substrates. Furthermore we present a dielectric antenna, which performs even better, due to the lack of losses by an appropriate choice of the dielectric material. These antennas are robust concerning fabrication tolerances and can be realized with different materials for both the antenna and the substrate, without using high index materials.
Keywords: tet_topic_opticalantenna

Influence of Coulomb-induced band couplings on linear excitonic absorption spectra of semiconducting carbon nanotubes - Liu, Hong; Schumacher, Stefan; Meier, Torsten (Physical Review B)
Starting from the extended Su-Schrieffer-Heeger model, multiband semiconductor Bloch equations are formulated in momentum space and applied to the analysis of the linear optical response of semiconducting carbon nanotubes (SCNTs). This formalism includes the coupling of electron-hole pair excitations between different valence and conduction bands, originating from the electron-hole Coulomb attraction. The influence of these couplings, which are referred to as nondiagonal interband Coulomb interaction (NDI-CI), on the linear excitonic absorption spectra is investigated and discussed for light fields polarized parallel to the tube direction. The results show that the intervalley NDI-CI leads to a significant increase of the band gap and a decrease of the exciton binding energy that results in a blueshift of the lowest-frequency excitonic absorption peak. The strength of these effects depends on the symmetry of the SCNT. Furthermore, for zigzag SCNTs with higher symmetry other nonintervalley NDI-CI terms also affect the spectral positions of excitonic absorption peaks.

Regeneration of Airy pulses in fiber-optic links with dispersion management of the two leading dispersion terms of opposite signs - Driben, R.; Meier, Torsten (Physical Review A)
Dispersion management of periodically alternating fiber sections with opposite signs of two leading dispersion terms is applied for the regeneration of self-accelerating truncated Airy pulses. It is demonstrated that for such a dispersion management scheme, the direction of the acceleration of the pulse is reversed twice within each period. In this scheme the system features light hot spots in the center of each fiber section, where the energy of the light pulse is tightly focused in a short temporal slot. Comprehensive numerical studies demonstrate a long-lasting propagation also under the influence of a strong fiber Kerr nonlinearity.

Femtosecond quantum interference control of electrical currents in GaAs: Signatures beyond the perturbative χ(3) limit - Sternemann, E.; Jostmeier, T.; Ruppert, C.; Duc, H. T.; Meier, Torsten; Betz, M. (Physical Review B)

Newton's cradles in optics: From N-soliton fission to soliton chains - Driben, R.; Malomed, B.A.; Yulin, A. V.; Skryabin, D.V. (Physical Review A)
A mechanism for creating a Newton's cradle (NC) in nonlinear light wave trains under the action of the third-order dispersion (TOD) is demonstrated. The formation of the NC structure plays an important role in the process of fission of higher-order (N) solitons in optical fibers. After the splitting of the initial N soliton into a nonuniform chain of fundamental quasisolitons, the tallest one travels along the entire chain, through consecutive collisions with other solitons, and then escapes, while the remaining chain of pulses stays as a bound state, due to the radiation-mediated interaction between them. Increasing the initial soliton's order, N, leads to the transmission through, and release of additional solitons with enhanced power, along with the emission of radiation, which may demonstrate a broadband supercontinuum spectrum. The NC dynamical regime remains robust in the presence of extra perturbations, such as the Raman and self-steepening effects, and dispersion terms above the third order. It is demonstrated that essentially the same NC mechanism is induced by the TOD in finite segments of periodic wave trains (in particular, soliton chains). A difference from the mechanical NC is that the TOD-driven pulse passing through the soliton array collects energy and momentum from other solitons. Thus, uniform and nonuniform arrays of nonlinear wave pulses offer an essential extension of the mechanical NC, in which the quasiparticles, unlike mechanical beads, interact inelastically, exchanging energy and generating radiation. Nevertheless, the characteristic phenomenology of NC chains may be clearly identified in these nonlinear-wave settings too.

Instabilities, solitons and rogue waves in PT-coupled nonlinear waveguides - Bludov, Y.V.; Driben, R.; Konotop, V.V.; Malomed, B.A. (Journal of Optics)
We considered the modulational instability of continuous-wave backgrounds, and the related generation and evolution of deterministic rogue waves in the recently introduced parity–time (P T)-symmetric system of linearly coupled nonlinear Schrödinger equations, which describes a Kerr-nonlinear optical coupler with mutually balanced gain and loss in its cores. Besides the linear coupling, the overlapping cores are coupled through the cross-phase-modulation term too. While the rogue waves, built according to the pattern of the Peregrine soliton, are (quite naturally) unstable, we demonstrate that the focusing cross-phase-modulation interaction results in their partial stabilization. For P T-symmetric and antisymmetric bright solitons, the stability region is found too, in an exact analytical form, and verified by means of direct simulations

Generation of tightly compressed solitons with a tunable frequency shift in Raman-free fibers - Driben, R.; Malomed, B.A. (Optics Letters)
Optimization of the compression of input 𝑁 -solitons into robust ultra-narrow fundamental solitons, with a tunable up- or downshifted frequency, is proposed in photonic crystal fibers free of the Raman effect. Due to the absence of the Raman self-frequency shift, these fundamental solitons continue propagation, maintaining the acquired frequency, once separated from the input 𝑁 soliton’s temporal slot. A universal optimal value of the relative strength of the third-order dispersion is found, providing the strongest compression of the fundamental soliton is found. It depends only on the order of the injected 𝑁 -soliton. The largest compression degree significantly exceeds the analytical prediction supplied by the Satsuma–Yajima formula. The mechanism behind this effect, which remains valid in the presence of the self-steepening, is explained.

Trapping of light in solitonic cavities and its role in the supercontinuum generation - Driben, R.; Yulin, A. V.; Efimov, A.; Malomed, B.A. (Optics Express)
We demonstrate that the fission of higher-order N-solitons with a subsequent ejection of fundamental quasi-solitons creates cavities formed by a pair of solitary waves with dispersive light trapped between them. As a result of multiple reflections of the trapped light from the bounding solitons which act as mirrors, they bend their trajectories and collide. In the spectral domain, the two solitons receive blue and red wavelength shifts, and the spectrum of the trapped light alters as well. This phenomenon strongly affects spectral characteristics of the generated supercontinuum. Consideration of the system's parameters which affect the creation of the cavity reveals possibilities of predicting and controlling soliton-soliton collisions induced by multiple reflections of the trapped light.

Inversion and tight focusing of Airy pulses under the action of third-order dispersion - Driben, R.; Hu, Y.; Chen, Z.; Malomed, B.A.; Morandotti, R. (Optics Letters)
By means of direct simulations and theoretical analysis, we study the nonlinear propagation of truncated Airy pulses in an optical fiber exhibiting both anomalous second-order and strong positive third-order dispersions (TOD). It is found that the Airy pulse first reaches a finite-size focal area as determined by the relative strength of the two dispersion terms, and then undergoes an inversion transformation such that it continues to travel with an opposite acceleration. The system notably features tight focusing if the TOD is a dominant factor. These effects are partially reduced by Kerr nonlinearity.

Nonlinear modes in binary bosonic condensates with pseudo–spin-orbital coupling - Zezyulin, D.A.; Driben, R.; Konotop, V.V.; Malomed, B.A. (Physical Review A)
We consider an effectively one-dimensional binary Bose-Einstein condensate (BEC) with nonlinear repulsive interactions and linear spin-orbit (SO) and Zeeman-splitting couplings. In the presence of the trapping harmonic-oscillator (HO) potential, we report the existence of even, odd, and asymmetric spatial modes. They feature alternating domains with opposite directions of the pseudospin, i.e., antiferromagnetic structures, which is explained by the interplay of the linear couplings, HO confinement, and repulsive self-interaction. The number of the domains is determined by the strength of the SO coupling. The modes are constructed analytically in the weakly nonlinear system. The dynamical stability of the modes is investigated by means of the Bogoliubov–de Gennes equations and direct simulations. A notable result is that the multi-domain-wall (DW) structures are stable, alternating between odd and even shapes, while the simplest single-DW structure is unstable. Thus, the system features a transition to the complex ground states under the action of the SO coupling. The addition of the Zeeman splitting transforms the odd modes into asymmetric ones via spontaneous symmetry breaking. The results suggest possibilities for switching the binary system between states with opposite (pseudo)magnetization by external fields, and realization of similar stable states and dynamical effects in solid-state and nonlinear-optical settings emulated by the SO-coupled BECs.

Soliton interaction mediated by cascaded four wave mixing with dispersive waves - Yulin, A. V.; Driben, R.; Malomed, B.A.; Skryabin, D.V. (Optics Express)
We demonstrate that trapping of dispersive waves between two optical solitons takes place when resonant scattering of the waves on the solitons leads to nearly perfect reflections. The momentum transfer from the radiation to solitons results in their mutual attraction and a subsequent collision. The spectrum of the trapped radiation can either expand or shrink in the course of the propagation, which is controlled by arranging either collision or separation of the solitons.

Collective effects in second-harmonic generation from split-ring-resonator arrays - Niesler, Fabian B.; Linden, Stefan; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, Martin (Conference on Lasers and Electro-Optics 2012)
We perform experiments on resonant second-harmonic generation from planar gold split-ring-resonator arrays under normal incidence of light as a function of the lattice constant. Optimum nonlinear conversion occurs at intermediate lattice constants.
Keywords: tet_topic_shg; tet_topic_meta

Optimal second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens (Ultrafast Phenomena and Nanophotonics XVII)
Previous experimental measurements and numerical simulations give evidence of strong electric and magnetic field interaction between split-ring resonators in dense arrays. One can expect that such interactions have an influence on the second harmonic generation. We apply the Discontinuous Galerkin Time Domain method and the hydrodynamic Maxwell-Vlasov model to simulate the linear and nonlinear optical response from SRR arrays. The simulations show that dense placement of the constituent building blocks appears not always optimal and collective effects can lead to a significant suppression of the near fields at the fundamental frequency and, consequently, to the decrease of the SHG intensity. We demonstrate also the great role of the symmetry degree of the array layout which results in the variation of the SHG efficiency in range of two orders of magnitude.
Keywords: tet_topic_shg; tet_topic_meta

Selection rules and linear absorption spectra of carbon nanotubes in axial magnetic fields - Liu, Hong; Schumacher, Stefan; Meier, Torsten (Physical Review B)
We derive a transparent and easy-to-use analytic expression for the selection rules and the optical dipole matrix elements for carbon nanotubes of arbitrary chirality in the presence of axial magnetic fields using a single-orbital π-electron tight-binding model. From this, we calculate the linear absorption spectrum for arbitrary polarization directions of the incident light, providing insight into all optically allowed transition. We show that the transverse absorption peaks can be selectively excited with circularly polarized light and spectrally resolved in an axial magnetic field.

Collective Effects in Second-Harmonic Generation from Split-Ring-Resonator Arrays - Linden, S.; Niesler, F. B. P.; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, M. (Physical Review Letters)
Optical experiments on second-harmonic generation from split-ring-resonator square arrays show a nonmonotonic dependence of the conversion efficiency on the lattice constant. This finding is interpreted in terms of a competition between dilution effects and linewidth or near-field changes due to interactions among the individual elements in the array.
Keywords: tet_topic_shg; tet_topic_meta

Excitonic Eigenstates of Disordered Semiconductor Quantum Wires: Adaptive Wavelet Computation of Eigenvalues for the Electron-Hole Schrödinger Equation - Meier, Torsten; Mollet, Christian; Kunoth, Angela (Communications in Computational Physics)
A novel adaptive approach to compute the eigenenergies and eigenfunctions of the two-particle (electron-hole) Schrödinger equation including Coulomb attraction is presented. As an example, we analyze the energetically lowest exciton state of a thin one-dimensional semiconductor quantum wire in the presence of disorder which arises from the non-smooth interface between the wire and surrounding material. The eigenvalues of the corresponding Schrödinger equation, i.e., the one-dimensional exciton Wannier equation with disorder, correspond to the energies of excitons in the quantum wire. The wavefunctions, in turn, provide information on the optical properties of the wire. We reformulate the problem of two interacting particles that both can move in one dimension as a stationary eigenvalue problem with two spacial dimensions in an appropriate weak form whose bilinear form is arranged to be symmetric, continuous, and coercive. The disorder of the wire is modelled by adding a potential in the Hamiltonian which is generated by normally distributed random numbers. The numerical solution of this problem is based on adaptive wavelets. Our scheme allows for a convergence proof of the resulting scheme together with complexity estimates. Numerical examples demonstrate the behavior of the smallest eigenvalue, the ground state energies of the exciton, together with the eigenstates depending on the strength and spatial correlation of disorder.

Photonic crystal waveguides intersection for resonant quantum dot optical spectroscopy detection - Song, Xiaohong; Declair, Stefan; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Optics Express)
Using a finite-difference time-domain method, we theoretically investigate the optical spectra of crossing perpendicular photonic crystal waveguides with quantum dots embedded in the central rod. The waveguides are designed so that the light mainly propagates along one direction and the cross talk is greatly reduced in the transverse direction. It is shown that when a quantum dot (QD) is resonant with the cavity, strong coupling can be observed via both the transmission and crosstalk spectrum. If the cavity is far off-resonant from the QD, both the cavity mode and the QD signal can be detected in the transverse direction since the laser field is greatly suppressed in this direction. This structure could have strong implications for resonant excitation and in-plane detection of QD optical spectroscopy.
Keywords: tet_topic_phc; tet_topic_qd

Near-field coupling and second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens
We simulate the linear and nonlinear optical response from split-ring resonator (SRR) arrays to study collective effects between the constituent SRRs that determine spectral properties of the second harmonic generation (SHG). We apply the Discontinuous Galerkin Time Domain (DGTD) method and the hydrodynamic Maxwell-Vlasov model to calculate the SHG emission. Our model is able to qualitatively reproduce and explain the non-monotonic dependence of the spectral SHG transmission measured experimentally for SRR arrays with different lattice constants
Keywords: tet_topic_meta; tet_topic_shg

Engineering high harmonic generation in semiconductors via pulse shaping - Reichelt, Matthias; Hildebrandt, Andre; Walther, Andrea; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XVI)
Paper Abstract High harmonic generation is investigated for a two-band model of a semiconductor nanostructure. Similar to an atomic two-level system, the semiconductor emits high harmonic radiation. We show how one can specifically enhance the emission for a given frequency by applying a non-trivially shaped laser pulse. Therefore, the semiconductor Bloch equations including the interband and additionally the intraband dynamics are solved numerically and the spectral shape of the input pulse is computed via an optimization algorithm. It is demonstrated that desired emission frequencies can be favored even though the overall input power is kept constant. We also suggest special metallic nano geometries to achieve enhanced localized optical fields. They are found by geometric optimization.
Keywords: tet_topic_shg

Tailoring the high-harmonic emission in two-level systems and semiconductors by pulse shaping - Reichelt, Matthias; Walther, Andrea; Meier, Torsten (Journal of the Optical Society of America B)
The generation of specific high harmonics for an optical two-level system is elucidated. The desired emitted radiation can be induced by a carefully designed excitation pulse, which is found by a multiparameter optimization procedure. The presented mechanism can also be applied to semiconductor structures for which the calculations result in much higher emission frequencies. The optimization procedure is either performed using a genetic algorithm or a rigorous mathematical optimization technique.

Numerical analysis of coupled photonic crystal cavities - Declair, S.; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
We numerically investigate the interaction dynamics of coupled cavities in planar photonic crystal slabs in different configurations. The single cavity is optimized for a long lifetime of the fundamental mode, reaching a Q-factor of ≈43, 000 using the method of gentle confinement. For pairs of cavities we consider several configurations and present a setup with strongest coupling observable as a line splitting of about 30 nm. Based on this configuration, setups with three cavities are investigated.
Keywords: tet_topic_phc

Application of the discontinous Galerkin time domain method to the optics of metallic nanostructures - Grynko, Yevgen; Förstner, Jens; Meier, Torsten (AAPP | Atti della Accademia Peloritana dei Pericolanti)
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. The model is used to compute the linear and nonlinear optical response of split ring resonators and to study physical mechanisms that contribute to second harmonic generation.
Keywords: tet_topic_numerics; tet_topic_shg; tet_topic_meta

Intensity-dependent ultrafast dynamics of injection currents in unbiased GaAs quantum wells - Pochwała, Michał; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (physica status solidi (RRL) - Rapid Research Letters)
The intensity dependence of optically-induced injection currents in unbiased GaAs semiconductor quantum wells grown in [110] direction is investigated theoretically for a number of well widths. Our microscopic analysis is based on a 14 x 14 band k . p method in combination with the multisubband semiconductor Bloch equations. An oscillatory dependence of the injection current transients as function of intensity and time is predicted and explained. It is demonstrated that optical excitations involving different subbands and Rabi flopping are responsible for this complex dynamics.
Keywords: tet_topic_qw